Consequences of the deactivation of the European Union’s fiscal rules and their reinstatement - Konc, Andraž (Oeconomica Jadertina, 2026)
This article examines the deactivation and the subsequent reinstatement of the European Union fiscal rules in response to the COVID-19 pandemic and its aftermath. It aimsto evaluate the macroeconomic and fiscal consequences of suspended fiscal rules and their role in addressing unprecedented economic challenges. A review-based methodology is employed, utilizing secondary data from authoritative sources, including the European Commission and Eurostat. The findings reveal that suspending fiscal rules enabled EU Member states to implement expansive fiscal measures, mitigating the pandemics economic impact but significantly inreasing public debt levels.Despite these interventions, disparities in fiscal responses and outcomes among Member States persist. We also highlight the challenges of reinstating fiscal rules amidst high debt levels and evolving economic conditions, emhasizing the need for flexibility and tailored approaches. Limitations include reliance on the aggreagate data and a lack of primary empirical evidence. Future research should focus on the long-term implications of reinstated fiscal rules on economic recovery, public investment and EUs green and digital transitions. Recommendations include improving fiscal governance frameworks to balance sustainability with flexiblity and enhancing compliance mechanisms for Member States.
Keywords: EU fiscal rules; COVID-19 pandemic; fiscal policy; economic governance; public debt